2021
DOI: 10.1007/s40751-021-00084-w
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Spatial Ability Through Computer-Aided Design: a Case Study

Abstract: Spatial ability is considered a major factor of intelligence and is increasingly important in times of digitization. This article explores the fostering of spatial ability through computer-aided design software. Different notions of spatial ability will be discussed, and, finally, a concept consisting of five aspects will be described. In addition, literature reviews on the connection between the use of computers and the fostering of spatial ability, as well as on the use of 3D printing technology in mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Compared with other such programs, Tinkercad inherits a particularly intuitive approach of modeling three-dimensional (3D) objects directly, providing easy access to such software for first-time users, such as elementary school students. As several research projects have already shown (Dilling & Vogler, 2021;Dilling & Witzke, 2020a, b;Gibson et al, 2014;Pielsticker, 2021;Pielsticker & Witzke, 2022;Ng, 2017;, this program affords students of all ages a good start in 3D printing technology.…”
Section: Cad Software: a Potential For Mathematics Educationmentioning
confidence: 91%
See 1 more Smart Citation
“…Compared with other such programs, Tinkercad inherits a particularly intuitive approach of modeling three-dimensional (3D) objects directly, providing easy access to such software for first-time users, such as elementary school students. As several research projects have already shown (Dilling & Vogler, 2021;Dilling & Witzke, 2020a, b;Gibson et al, 2014;Pielsticker, 2021;Pielsticker & Witzke, 2022;Ng, 2017;, this program affords students of all ages a good start in 3D printing technology.…”
Section: Cad Software: a Potential For Mathematics Educationmentioning
confidence: 91%
“…Another recent case study by Dilling and Vogler (2021) provides insight into the possibilities of fostering spatial ability through such software in secondary school. In the study by Ng (2017), the CAD software and 3D printing are used for teaching about the volume of solids in junior secondary mathematics classrooms.…”
Section: Cad Software: a Potential For Mathematics Educationmentioning
confidence: 99%
“…Compared to other programs of this type, Tinkercad includes a particularly intuitive approach to directly modeling three-dimensional (3D) objects and provides easy access to such software for first-time users such as primary school students. As several research projects have already shown, this program provides students of all ages with a good start in 3D printing technology (Dilling & Vogler, 2021; Ng et al, 2018; Pielsticker, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Spatial visualization is the art of visualizing 2-and 3-dimensional objects in one's mind. At rest and in motion, spatial orientation is the capacity to maintain our bodily orientation and posture concerning the surrounding environment (physical space) [8]. According to research, spatial thinking skills and geometric reasoning are essential to the development of problem-solving abilities, mathematics learning, and reading [9,10].…”
Section: Introductionmentioning
confidence: 99%